Implementasi Metode Design Thinking Dalam Membangun Aplikasi Prodi Pilihanku - Yarza Aprizal; Mahmud; Veronica, Maria; Mahendra, Agung; Kristian, Billy; Serliyawati, Ellicia (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
The results of a survey conducted by the Indonesian Career Center Network (ICCN) in 2017 showed that 87% of Indonesia’s students stated that the field of study they chose did not match their interests. Based on the results of this survey, as well as the observations and findings emerging from the research environment, it is a motivation for researchers to develop applications of interest and talent tests. The design thinking method applied consists of five stages, namely, emphasize, define, imagine, prototype, and test, and has produced a minimum viable product (MVP) called Prodi P. The resulting MVP has three main features are interest and talent tests, product information, and consultation. The test results of the MVP are carried out in two ways: alpha testing and beta testing. The results of alpha testing indicated that 100% of the application features met the requirements, while beta testing stated that the application was attractive and provided positive information, and 91.6% of visitors declared that the provided test tools were relevant to the characteristics of the computer science program.In conclusion, the app has been running according to the user's expectations.